Accelerating Campylobacter zoonosis in the Anthropocene - Oakem J. Kyne; Bridget S. Penman; David J. Kelly; Samuel K. Sheppard (Proceedings of the National Academy of Sciences, 2026)
Intensive poultry farming has transformed global bird populations, concentrating billions of chickens into dense industrial systems that fundamentally reshape ecological space. As birds are important pathogen reservoirs, these changes can have important consequences for the spread of zoonoses including Campylobacter jejuni —the leading cause of bacterial gastroenteritis. Analyzing 2,747 genomes from chickens and wild birds, we show that poultry intensification has eroded historic host–strain associations and created a new and expanding ecological niche. Phylogenetic reconstructions reveal an estimated 100-fold increase in chicken-to-wild-bird host transitions since 1900 compared to predomestication levels, alongside dramatic post-1960 expansions of chicken-associated lineages and rising pathogen effective population sizes. Model simulations further indicate that expanding, high-density chicken populations could act as ecological “pathogen sponges,” absorbing and amplifying diverse strains while sustaining high prevalence and coinfection rates. Genome-wide association analyses show that strains adapted to the chicken niche frequently acquire genes linked to oxidative stress, metal homeostasis, motility, and antimicrobial resistance. Together, these findings demonstrate that intensive poultry farming is reshaping pathogen ecology and accelerating the evolution and spread of a major zoonotic bacterium, with direct implications for human health.